Situation Of Fluorides Rate In Waters And Major Consumed Food In Wilaya El-oued - Zobeidi, A.; Messiatfa, A. (University of Eloued جامعة الوادي, 2010)
The effects of mineral salts in the drinking water, beneficial or harmful depending on their concentration, are known for many years and thus the problem posed by fluoride ions in the waters of the region (Fluorosis Dental and skeletal). This study proposes, the estimated daily intake of fluoride from its water distribution and the main food consumed per capita in the region of El-Oued (dates, tea, couscous, lentils, carrots, potatoes, pumpkin ...), which has a significant content of fluoride in their composition. In addition to the arid climatic conditions, the air temperature is very high in summer, leads to a strong human perspiration. This preliminary result leads us to propose a standard fluoride-specific region of El-Oued. The results showed that the majority of water samples and analyzed the main foods of the region of El-Oued is charged fluoride ions and exceed the maximum dose recommended for adults from 0.05 to 0.07 mg / kg / day.
Articale in Journal of fundamental and Applied Sciences Vol. 02 N. 02
Keywords: Water, Food, El-Oued, fluoride, chemical balance